The Intestine as a Lifespan- and Proteostasis-Promoting Signaling Tissue - Hodge, Francesca; Bajuszova, Viktoria; van Oosten-Hawle, Patricija (Frontiers in Aging, 2022)
In multicellular organisms such as Caenorhabditis elegans, cellular stress stimuli and responses are communicated between tissues to promote organismal health- and lifespan. The nervous system is the predominant regulator of cell nonautonomous proteostasis that orchestrates systemic stress responses to integrate both internal and external stimuli. This review highlights the role of the intestine in mediating cell nonautonomous stress responses and explores recent findings that suggest a key role for the intestine to regulate organismal proteostasis. As a tissue that receives and further transduces signals from the nervous system in response to dietary restriction, heat- and oxidative stress, and hypoxia, we explore evidence suggesting the intestine is a central regulatory organ itself. By shifting the perspective to naturally occurring stressors such as dietary restriction and pathogen infection we highlight how the intestine can function as a key regulator of organismal proteostasis by integrating insulin-like signaling, miRNA-, neuropeptide- and metabolite signaling to alter distal tissue functions in promoting survival, health- and lifespan.